Performance evaluation of entrepreneurship teachers in accounting vocational program - Irena Puspitaningratri; Nur Hidayanto Pancoro Setyo Putro (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2021)
This study aimed to discover the teachers' performance of the PKK Accounting Expertise Program at State SMK 1 Samigaluh based on primary duties. This study was an evaluation using the discrepancy evaluation model. The study subjects were PKK teachers of State SMK 1 Samigaluh. Information sources for the study were the headmaster, six colleagues, and 52 students. The instruments used were questionnaires, assessment sheets, and documentation sheets. The headmaster presented an excellent assessment of the PKK subject teachers of 92.81. In contrast to the headmaster, colleagues and students presented good assessments of the PKK subject teachers. According to colleagues, the PKK subject teachers' performance assessment was 86.42, while, according to students, it was 86.67. Based on the average performance assessment, the PKK teachers of Accounting Expertise and Institutional Financial at State SMK 1 Samigaluh were categorized as good. The headmaster presented the highest score than other assessments on all primary duties.